Criteria for Selection and Evaluation of Rolling Stock of Motor Transport Enterprises - Khavruk, V. O; Parkhomenko, O. O (Science and Transport Progress, 2021)
Purpose. The basic aim of the work is to analyze and substantiate the criteria for selection and evaluation of rolling stock – trucks of motor transport enterprises, based on scientific research on this issue. Methodology. The research was performed using general methods: abstraction and concretization, analysis, synthesis, induction, deduction. Findings. It is established that the main features of the classification of criteria for selection and evaluation of rolling stock are the number of factors (there are single and complex criteria); level of dependence (it is possible to single out completely dependent on external operating conditions, partially dependent and independent criteria); nature (quantitative and qualitative criteria); quantitative value (absolute and relative criteria). The practical approach at a choice of rolling stock fleet for the motor transport enterprise, proceeding from such factors, as character and structure of cargo flow; volumetric weight and batch of cargo; road conditions; ensuring maximum speed and traffic safety; ensuring the minimum costs associated with goods transportation. The scheme of criteria for the selection of rolling stock is presented and five stages are clarified, which establish the sequence of evaluation and selection of vehicles: 1) analysis of transportation conditions and cargo characteristics; 2) the choice of car capacity; 3) structure suitability analysis to the road conditions; 4) analysis of technical and operational properties of cars; 5) technical and economic evaluation of cars selected in the first four stages, which can be performed according to different criteria. The expediency of bringing different criteria into one complex quality indicator is performed in a graphical interpretation. It was found that the technical and economic evaluation of cars is based on the following criteria: car performance; the complexity of using the car; energy consumption of transportation; metal consumption of transportations. Originality. The analysis of the criteria for selection and evaluation of rolling stock allowed to form a method of selection and evaluation of vehicles and the criteria used in the form of a structured scheme that takes into account the main goal – to maximize profits from transport work and minimize operating costs. Practical value. The results of the study can be used by motor transport enterprises in the selection of rolling stock at the stages of purchase of new trucks, based on the practical experience of transportation of various types of goods.